Prof. Yih-Sharng Chen: a new era—to breakthrough the old times - Fan, Wei-En (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Professor Chen is the Chairman of Cardiovascular Surgery Division in National Taiwan University Hospital since 2010. He is also the Chair Elect of Asia-Pacific ELSO. He finished his medical education and training in National Taiwan University Hospital and overseas. His research interests focus on pediatric cardiac surgery, coronary artery bypass grafting (CABG) and heart valve surgery. He is not only a talented pediatric surgeon, but also a pioneer in the use of extracorporeal membrane oxygenation (ECMO) for patients with postcardiotomy cardiogenic shock in Taiwan. The study has benefitted numerous lives ever since. And it shows an increasing survival rate for the patients with this ‘life-saving’ treatment (Figure 1).